2009
DOI: 10.1097/jto.0b013e3181bbf239
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Mutations Detected in Plasma Are Associated with Patient Outcomes in Erlotinib Plus Docetaxel-Treated Non-small Cell Lung Cancer

Abstract: Activating EGFR mutations detected in shed DNA in plasma are significantly associated with favorable outcomes in patients with advanced NSCLC receiving docetaxel plus intercalated erlotinib. The addition of docetaxel in this schedule did not diminish the efficacy of erlotinib against patients with EGFR activating mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 35 publications
6
54
2
2
Order By: Relevance
“…Subsequent studies have attempted to confirm these results in a larger case series (75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89). Using different methodologies, results of the majority of those studies identified identical serum/plasma, with tissue EGFR mutations being reported in >70% of patients (74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89) (Table I).…”
Section: Biological Samples Suitable For Molecular Characterisationmentioning
confidence: 63%
“…Subsequent studies have attempted to confirm these results in a larger case series (75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89). Using different methodologies, results of the majority of those studies identified identical serum/plasma, with tissue EGFR mutations being reported in >70% of patients (74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89) (Table I).…”
Section: Biological Samples Suitable For Molecular Characterisationmentioning
confidence: 63%
“…The sensitivity of direct sequencing is relatively poor and requires more mutant DNA to detect EGFR mutations in specimens (10-25% mutant DNA). The PNA-LNA PCR clamp is more sensitive and is able to detect ≥1% mutant DNA in the specimens, as is the Scorpion Amplified Refractory Mutation System (ARMS) method, which currently has kits commercially available for testing (4,10,12,14). However, direct sequencing is able to detect new mutations, while the PNA-LNA PCR clamp and the Scorpion ARMS are capable of detecting known mutations only (10,12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Determination of the tumor EGFR mutation status is significant for non-squamous NSCLC, since first-line treatment with erlotinib or gefitinib is recommended for patients with EGFR-activating mutations, and cytotoxic chemotherapy is recommended for patients without an EGFR-activating mutation status or with an unknown status. The use of plasma or serum samples for EGFR mutation analysis has been actively studied recently since more than half of the patients did not have or had inadequate pathological samples for tumor EGFR mutation analysis (9,10). Several methods are used to detect EGFR mutations in lung cancer specimens (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…105 Subsequent studies have attempted to confirm these results in larger case series. [106][107][108][109][110][111][112] Indeed, using a range of different methodologies, serum/plasma EGFR mutations have been reported in over 70% of patients in which the tumor tissue showed the same mutation (Table 2).…”
Section: Biological Samples Suitable For Molecular Characterizationmentioning
confidence: 99%